Sistem Penunjang Keputusan Keikutsertaan SNMPTN Bagi Siswa SMAN 1 Kerinci - Hamsiah, Hamsiah; Zamidra Zam, Efvy (Jurnal Pseudocode, 2024)
The school decides for students who take part in SNMPTN (National Selection for State University Entrance). SNMPTN participation is determined based on learning results for semesters 1-5. Based on the LTMPT (Higher Education Entrance Test institution) rules, participation in SNMPTN can be determined based on achievements and other scores that can support selection. The aim of this research is to produce a decision support system that will be used in determining student participation in SNMPTN. The method used in this research is the SDLC method with the waterfall model. Waterfall or the waterfall model is a classic, systematic life cycle model in developing software. The calculation process uses Analytical Hierarchy Process (AHP) with the variables of report card grades, achievements and school accreditation. The results obtained show that the report card score, namely 0.721 or 72%, is the highest criterion that influences students to be able to take part in the SNMPTN route and applications that can help in the selection process for the SMAN 1 Kerinci school.